Extracellular Vesicles Derived From Human Corneal Endothelial Cells Inhibit Proliferation of Human Corneal Endothelial Cells - Parekh, Mohit; Rhys, Hefin; Ramos, Tiago; Ferrari, Stefano; Ahmad, Sajjad (Frontiers in Medicine, 2022)
Corneal endothelial cells (CEnCs) are a monolayer of hexagonal cells that are responsible for maintaining the function and transparency of the cornea. Damage or dysfunction of CEnCs could lead to blindness. Human CEnCs (HCEnCs) have shown limited proliferative capacity in vivo hence, their maintenance is crucial. Extracellular vesicles (EVs), are responsible for inter- and intra-cellular communication, proliferation, cell-differentiation, migration, and many other complex biological processes. Therefore, we investigated the effect of EVs (derived from human corneal endothelial cell line – HCEC-12) on corneal endothelial cells. HCEC-12 cells were starved with serum-depleted media for 72 hours. The media was ultracentrifuged at 100,000xg to isolate the EVs. EV counting, characterization, internalization and localization were performed using NanoSight, flow cytometry, Dil labelling and confocal microscopy respectively. HCEC-12 and HCEnCs were cultured with media supplemented with EVs. Extracted EVs showed a homogeneous mixture of exosomes and microvesicles. Cells with EVs decreased the proliferation rate; increased apoptosis and cell size; showed poor wound healing response in vitro and on ex vivo human, porcine, and rabbit CECs. Thirteen miRNAs were found in the EV sample using next generation sequencing. We observed that increased cellular uptake of EVs by CECs limit the proliferative capacity of HCEnCs. These preliminary data may help in understanding the pathology of corneal endothelial dysfunction and provide further insights in the development of future therapeutic treatment options.